Exploring the microbial diversity and functional potential of Domas Crater of Mount Tangkuban Perahu, Indonesia, through shotgun metagenomics - HARYONO BUDI SANTOSO; ANTONIUS SUWANTO; RAHADIAN PRATAMA (Society for Indonesian Biodiversity, 2024)
Abstract. Santoso HB, Suwanto A, Pratama R. 2024. Exploring the microbial diversity and functional potential of Domas Crater of Mount Tangkuban Perahu, Indonesia, through Shotgun Metagenomics. Biodiversitas 25: 4613-4626. Domas Crater, an extreme environment in Indonesia, is known for high temperatures and acidic conditions, providing a unique habitat for specialized microbial communities. These extreme conditions increase the possibility of discovering thermophilic enzymes with valuable biotechnological applications. Therefore, this study aimed to explore the microbial diversity in Domas Crater using shotgun metagenomics to analyze both previously reported microbes and novel microorganisms comprehensively. Shotgun metagenomics is particularly advantageous in identifying microbial species that cannot be cultured using conventional methods, enabling the exploration of microorganisms with considerable potential. The application of next-generation sequencing technologies and bioinformatics tools allowed the successful reconstruction of eight high-quality Metagenome-Assembled Genomes (MAGs), a testament to the technical proficiency of the study. The genomes were further characterized based on the functional genes, including the enzymes in carbohydrate metabolism or Carbohydrate-active enzymes (CAZyme), biosynthetic gene clusters for secondary metabolite (BGCs), and genes associated with micronutrient metabolism. The results showed that the microbial community was dominated by Hydrogenobaculum and Sulfurisphaera, both known for adaptation to extreme environments. Moreover, the first Hydrogenobaculum and Thermocladium were recorded in Indonesia as the novel discoveries of the study. These findings highlight the significance of Domas Crater as a reservoir for novel microbial species, particularly in terms of thermophilic microorganisms with unique enzymatic properties.